Synthesizing high purity nano crystalline Y2O3 powder for transparent ceramics - Shawn Berqmans Pereira (Nanyang Technological University, 2021)
Usage of nanomaterials are being more popular due the growth in usage of ceramics. Yttrium Oxide (Y2O3) is one of the nanomaterials that has been widely used in ceramics. It is mainly due to giving its host material ideal physical and chemical properties such as having high melting point, a broad transparency range, corrosion resistance, etc. [1] Before fabrication of yttria ceramics, the Y2O3 powder has to first be synthesized to provide adequate properties to its host material. There are plenty of methods in synthesizing of Y203 powder. The scope of this project is carrying out experiments to synthesize high quality Y203 powder for laser ceramic fabrication. A much efficient technique would be designed using references from previously done techniques that may cut time and costs involved but producing an Y203 powder with better required qualities. Further research could be applied, and recommendations were suggested to improve on future research.